Macroeconomic Drivers of Inflation in Ethiopia: Evidence from ARDL Modelling - Ayal, Betselot; Bekalu, Kassa; Ayenalem, Mullugeta (Journal Economic Business Innovation, 2024)
Purpose: This study identifies the macroeconomic determinants of inflation in Ethiopia from 2012 to 2023, a period marked by reforms and liberalization efforts. Despite these measures, inflation remains a critical challenge impacting Ethiopia's economic stability.Method: Utilizing the ARDL model, this study examines the relationship between inflation and various macroeconomic indicators. Data are drawn from sources such as the National Bank of Ethiopia (NBE), Ethiopian Economic Association (EEA), International Monetary Fund (IMF), and World Bank (WB). The Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) tests are employed to assess data stationarity.Findings: Results indicate that money supply growth, import-to-GDP ratio, budget deficit, and public expenditure have a significant positive effect on inflation in both the long and short term. Conversely, lending interest rates exhibit inflationary effects in the short term but are deflationary in the long term. Additionally, external debt-to-GDP ratio, official exchange rate, and real GDP growth rate demonstrate negative long-term impacts on inflation.Novelty: This research uniquely integrates key macroeconomic variables, analyzing their divergent impacts on inflation across short- and long-term frameworks in Ethiopia's context.Implications: The findings underscore the importance of balanced fiscal and monetary policies to curb inflation, offering critical insights for Ethiopian policymakers aiming to foster economic stability.